Probing the lubricating mechanism of oil-soluble ionic liquids additives - Huang, Guowei; Yu, Qiangliang; Ma, Zhengfeng; Cai, Meirong; liu, Weimin (Tribology international, 2017)
To clarify the lubricating mechanism, two kinds of oil-soluble ionic liquids (ILs) with the same cation but different anions are synthesized, and then they are added into PAO10 as additives with different mass concentration. The tribological results indicate that the mixtures perform better lubricating performance than neat PAO10 for steel/steel contacts. Then quartz crystal monitor (QCM), X-ray photoelectron spectroscopy (XPS), plasma treatment, and external potential are introduced to clarify the lubricating mechanism of ILs as additives. The lubricating mechanism of the kind of ILs can be attributed to the good adsorptivity of cations and tribochemical films on the sliding surfaces. The lubrication mechanism of ILs as the lubricant additive for the steel–steel contact. [Display omitted] •Two kinds of oil-soluble ionic liquids (ILs) with the same cation but different anions are synthesized, which exhibit more favourable solubility property in PAO10 than tradition ILs.•The tribological results indicate that the mixtures perform excellent lubricating performance compared with neat PAO10 for steel/steel contacts.•Many characterization methods, such as quartz crystal monitor (QCM), plasma treatment, external potential and X-ray photoelectron spectroscopy (XPS), are applied comprehensively to clarify the lubricating mechanism of ILs as additives.